Mengurai Riset tentang Inisiatif Zakat Indonesia - Najiba, Sumayyah; Handoko, Luqman Hakim; Baehaqi, Ahmad (IQTISHODUNA, 2025)
This study aims to analyze the bibliometric research on the Indonesian Zakat Initiative (IZI) indexed in Google Scholar. The research method used is bibliometric analysis and a Systematic Literature Review (SLR) with the PRISMA approach. Data was obtained through Publish or Perish (PoP) using the keywords "Indonesian Zakat Initiative" and "LAZ IZI." The analysis was conducted using VOSviewer software to identify research trends based on available publications in the database.The results show that there are 81 articles on IZI that have developed from 2018 to 2024. The highest case distribution is in Java Island (54%, 42 articles). The most productive author is ES Bahri (3 articles), while the most productive institution is UIN Sumatera Utara (10 articles). The most productive journal is Jurnal Ekonomi Syariah Teori dan Terapan, with five relevant publications. One of the most influential collaborative articles is titled Web-Based Information System for Managing Zakat, Infak, and Sedekah Beneficiaries, with 175 citations. Research trends were analyzed through network visualization, overlay visualization, and density visualization to reveal research patterns. The co-occurrence analysis identified 32 future research topics, such as IZI zakat program effectiveness and financial transparency. Meanwhile, the SLR analysis identified five main topics, one of which is related to factors influencing zakat fund acceptance by mustahik and its impact on their welfare.